Cross-cultural Strategic PR Practices of Multinational Corporations in the Context of Globalization and The Effectiveness Evaluation - Yu, Yang (Transactions on Economics, Business and Management Research, 2024)
In the process of globalization, the operations and management of multinational corporations (MNCs) are increasingly affected by different cultural environments. The purpose of this article is to explore the key strategies employed by MNCs in implementing cross-cultural strategic PR practices and to provide an in-depth assessment of the effectiveness of these practices. The article will analyze the challenges faced by MNCs in formulating and implementing cross-cultural PR policies, including language barriers, value differences, adaptation of legal systems, and localization implementation. Through case studies of a number of internationally renowned multinational corporations, it will show how they have successfully implemented cross-cultural PR activities by building a diverse and inclusive corporate culture, customizing communication content to match local culture, and building effective multilateral communication mechanisms.